Long-Term Effects of Equal Sharing: Evidence from Inheritance Rules for Land - Charlotte Bartels; Simon Jäger; Natalie Obergruber (Center for Economic Studies and ifo Institute (CESifo), 2024)
What are the long-term economic effects of a more equal distribution of wealth? We investigate consequences of land inequality, exploiting variation in land inheritance rules that traverse political, linguistic, geological, and religious borders in Germany. In some German areas, inherited land was to be shared or divided equally among children, while in others land was ruled to be indivisible. Using a geographic regression discontinuity design, we first show a more equal land distribution in areas with equal division; other potential drivers of growth are smooth at the boundary and equal division areas were not historically more developed. Today, equal division areas feature higher average incomes and more entrepreneurship which goes in hand with a right-shifted skill, income, and wealth distribution. We show evidence consistent with the more even distribution of land leading to more innovative industrial by-employment during Germany's transition from an agrarian to an industrial economy that, in the long-run, led to more entrepreneurship.
Keywords: 330